Designing Learning Trajectory of Curved 3D Shapes using RME with The Context of Sesaji Rewanda Semarang - Tuni'mah, Lattifah; Nursyahidah, Farida; Albab, Irkham Ulil; Rubowo, Maya Rini (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2024)
Curved 3D shapes are one of the essential materials in geometry, but students have difficulty learning the material. Thus, this study aimed to describe a learning trajectory to aid students in comprehending curved 3D shapes in the context of the Sesaji Rewanda tradition. The method used is design research with the RME learning approach as developed by McKenney and Akker. The subject in this research is the 9th grade of SMP Negeri 6 Semarang. The resulting learning trajectory comprised 5 sets of activities, namely: (1) identifying the types and characteristics of curved 3D shapes, (2) determining the beginning of the formulas for cylinder surface area and volume, (3) determining the beginning of the formulas for cone surface area and volume, (4) determining the beginning of the formulas for sphere surface area and volume, and (5) resolve contextual problems associated to curved shapes. The 5 activities produced in this study are hopefully to encourage students to learn and become an inspiration for teachers in implementing learning.